Skrening Resistensi Antibiotik Pada Bakteri Asam Laktat yang Diisolasi dari Usus Ayam Pedaging - Nurbaiti Nurbaiti; Anwar Rosyidi; Muhamad Ichsan; Muhamad Ali (Faculty of Animal Husbandry, University of Mataram, 2018)
Antibiotic use in poultry production is commonly performed as the feed additive for promoting the health and growth of the chicken. However, excessive use of antibiotics may lead to the emergence of antibiotic resistance in Escherichia coli, lactic acid bacteria, and pathogenic bacteria. In this research, screening of antibiotic resistance was assayed on lactic acid bacteria obtained from broiler intestine. Among the 14 lactic acid isolates, 2 (14%) isolates were found to be resistant to chloramphenicol. Resistance was also observed to ampicillin and kanamycin (7%). The result of this research indicated that the overuse and misuse of antibiotics in broiler farm tend to generate antibiotic resistance in broiler’s intestine lactic acid bacteria. Therefore, some advice for safety measure of antibiotic application in poultry farmer is strongly necessary.